Pemanfaatan Pelayanan Posyandu sebagai Faktor Risiko Dominan Kejadian Gagal Tumbuh pada Balita di Wilayah Puskesmas Pringsurat: Posyandu Service Utilization as a Dominant Risk Factor for Under-Five Faltering Growth in the Area of Pringsurat Community Health Center - Putri, Diah Aprilia; Suyatno, Suyatno; Fatimah, Siti (Amerta Nutrition, 2024)
Background: Faltering growth is a precursor to nutritional problems, yet government efforts often fail to address region-specific causes. The agricultural area of Pringsurat Community Health Center has the highest incidence of faltering growth in Temanggung Regency. Objectives: This study aimed to analyze the risk factors for faltering growth in children under five in the area of Pringsurat Community Health Center. Methods: This study employed a case-control design involving 104 children (52 with growth failure and 52 without). Subjects were randomly selected from integrated service posts (posyandu) in villages with the highest cases of growth failure within the research area. Growth failure was defined by a stagnant weight-for-age z-score (WAZ) across three weight measurements. Data on growth failure were collected through weight measurements, while data on factors associated with growth failure were obtained from interviews and the Maternal and Child Health (MCH) book records. Statistical analysis was performed using chi-squared and logistic regression tests. Results: The majority of the subjects were female, aged 24-59 months, had normal birth weight, had a history of infections, utilized posyandu services, received good parenting, and consumed insufficient energy but adequate protein. The main risk factor for failure to thrive was posyandu service underutilization (OR=2.564; 95% CI [1.163-5.654]; p-value=0.019). Factors such as parenting practices, a history of infection, birth weight, gender, and protein consumption were not statistically significant. Conclusions: Posyandu service underutilization is the predominant risk factor for growth failure among children under five in the area of Pringsurat Community Health Center.